Chirality Transfer from an Innately Chiral Nanocrystal Core to a Nematic Liquid Crystal 2: Lyotropic Chromonic Liquid Crystals. Issue 3 (25th October 2022) - Gonçalves, Diana P. N.; Ogolla, Timothy; Hegmann, Torsten
Abstract: The importance of and the difference between molecular versus structural core chirality of substances that form nanomaterials, and their ability to transmit and amplify their chirality to and within a surrounding condensed medium is yet to be exactly understood. Here we demonstrate that neat as well as disodium cromoglycate (DSCG) surface‐modified cellulose nanocrystals (CNCs) with both molecular and morphological core chirality can induce homochirality in racemic nematic lyotropic chromonic liquid crystal ( rac ‐N‐LCLC) tactoids. In comparison to the parent chiral organic building blocks, D‐glucose, endowed only with molecular chirality, both CNCs showed a superior chirality transfer ability. Here, particularly the structurally compatible DSCG‐modified CNCs prove to be highly effective since the surface DSCG moieties can insert into the DSCG stacks that constitute the racemic tactoids. Overall, this presents a highly efficient pathway for chiral induction in an aqueous medium and thus for understanding the origins of biological homochirality in a suitable experimental system. Abstract : Cellulose nanocrystals (CNCs), neat or surface‐modified with a mesogenic motif, transmit their inherent molecular and morphological chirality to a racemic nematic lyotropic chromonic liquid crystal ( rac ‐N‐LCLC) medium with the resulting optical activity values being nine‐ to fourteen‐fold higher than those obtained for neat, parent D‐glucose as the building block of CNCs. Nanoscale chirality combined with suitable surface functionalization emerges as a powerful tool and opens pathways for earth‐abundant and renewable chiral dopants.